Lietuvių asmenvardžių sąveika - Zinkevičius, Zigmas (Baltistica, 2009)
INTERACTION OF LITHUANIAN PERSONAL NAMES The article examines the three layers of the origin of Lithuanian personal names, i. e. the layer of the old national onomastics, the layer of personal names brought by Christianity and the layer of nicknames, and the interplay between these layers. The intrusion of Christian names into the old system of two-stem personal names and the impact of the latter on Christian names is highlighted, as well as the interaction between the Christian onomastics and that of the origin of nickname. Hybrid forms are also discussed.